Clonotypic CD20+ and CD19+ B cells in peripheral blood of patients with multiple myeloma post high-dose therapy and peripheral blood stem cell transplantation - Rottenburger, Christof; Kiel, Katja; Bösing, Tobias; Cremer, Friedrich Walter; Moldenhauer, Gerhard; Ho, Anthony Dick; Goldschmidt, Hartmut; Moos, Marion (British journal of haematology, 1999)
The number of circulating clonotypic B cells in patients with multiple myeloma (MM) after high-dose therapy (HDT) with peripheral blood stem cell transplantation (PBSCT) was investigated. Peripheral CD19+ B cells have been reported to persist throughout conventional and HDT and might resemble a source of relapse in patients with MM. We assessed the proportion of malignant cells in CD20+ and CD19+ cell fractions of 14 peripheral blood (PB) samples from 12 patients after HDT and PBSCT. Nine samples were obtained from patients in continuous remission, and five patients were in progressive disease or beginning relapse. The CD20+ fractions obtained had a mean purity of 96.8%. The percentages of tumour cells were determined using a quantitative allele-specific oligonucleotide PCR assay based on the method of limiting dilutions. In the group of patients in continuous remission the median number of tumour cells in the CD20+ cell fractions was 1.9/ml (range 0-7.2 tumour cells/ml PB) higher than in the CD20− fractions (median 0; range 0-29 tumour cells/ml PB). Higher tumour cell numbers in both fractions, particularly pronounced in the negative ones, were found in patients with progressive disease or beginning relapse (CD20+: range 3.8-585; median 32 tumour cells/ml PB; CD20−: range 25-25527; median 334 tumour cells/ml PB). Enrichment with the anti-CD19 antibody as a second pan B-cell marker revealed comparable tumour cell numbers. In conclusion, an anti-CD20 antibody treatment could be a promising approach for the eradication of malignant cells in the PB of patients in continuous remission after HDT and PBSCT with low amounts of tumour cells in the B-cell compartment and an almost complete absence of tumour cells in the CD20− fractions.
Elektronische Reproduktion der Druckausgabe
Die Pluszeichen im Titel sind hochgestellt
Gesehen am 10.12.2021